Strövtåg i komponerandets landskap : tre studier av komponerande med hjälp av dator och musikteknologi - Vesterlund, Lena Lundberg (Luleå tekniska universitet, Musik och dans, 2001)
The purpose of the thesis is to make visible and to give an insight in composing processes leading up to new music compositions. The overarching purpose was to study how men and women composed music with the aid of computers and music technology, and how they talked about their composing. The thesis is divided into three parts. The empirical study is based on a distance project, where folk high school students were given the task to compose music in four given styles; chopin, blues, bach and jazz style. Furthermore, the first and the last tasks were free. The compositions were sent as a MIDI file to supervisors at the School of Music in Piteå for comments. Participants were ten music students, evenly divided among two folk high schools, and five teachers in music theory at a school of music. Data consists of introduction inquiry, recorded music pieces as well as interviews. The result shows that the students talk about three main conditions, which are important for the composing work: previous knowledge (music, music technology, computer), creativity and gender. Regarding concepts connected with composing the language tends to change with composing genre and tools. The participants talk of both positive and negative effects of using computer and music technology as a tool for composing. One further result was that "given" tasks in many cases opened up for greater creativity in comparison with the free tasks. Finally, gender differences were proved by the fact that the women showd less self-confidence and were more critical about their composing than the men. The women also followed task instructions more carefully. This work concludes with a discussion about what the introduction of new technique might involve for music pedagogy as well as what kind of knowledge might be relevant for the future. Godkänd; 2001; 20061114 (haneit)